A New Generalization on Cauchy-Schwarz Inequality. (13th June 2017) - Yin, Songting
Abstract : We extend the well-known Cauchy-Schwarz inequality involving any number of real or complex functions and also give a necessary and sufficient condition for the equality. This is another generalized version of the Cauchy-Schwarz inequality.